Maternal immunisation: collaborating with mother nature. Issue 7 (July 2017) - Marchant, Arnaud; Sadarangani, Manish; Garand, Mathieu; Dauby, Nicolas; Verhasselt, Valerie; Pereira, Lenore; Bjornson, Gordean; Jones, Christine E; Halperin, Scott A; Edwards, Kathryn M; Heath, Paul; Openshaw, Peter J; et al.
Summary: Maternal immunisation has the potential to substantially reduce morbidity and mortality from infectious diseases after birth. The success of tetanus, influenza, and pertussis immunisation during pregnancy has led to consideration of additional maternal immunisation strategies to prevent group B streptococcus and respiratory syncytial virus infections, among others. However, many gaps in knowledge regarding the immunobiology of maternal immunisation prevent the optimal design and application of this successful public health intervention. Therefore, we did an innovative landscape analysis to identify research priorities. Key topics were delineated through review of the published literature, consultation with vaccine developers and regulatory agencies, and a collaborative workshop that gathered experts across several maternal immunisation initiatives—group B streptococcus, respiratory syncytial virus, pertussis, and influenza. Finally, a global online survey prioritised the identified knowledge gaps on the basis of expert opinion about their importance and relevance. Here we present the results of this worldwide landscape analysis and discuss the identified research gaps.